Europe, Scandinavia and Baltic Republics' Future (Czech Journal of International Relations, 1994)
What do the Baltic states expect from Europe? The answer is quite simple. The Baltic nations want Europe and the West to understand their not easy situtation, and also help so that they can help themselves. That's about it. But then the question arises: What is their situation? What solutions can they choose from? And why should the West actually help them?If we want to answer these questions, it is necessary to examine the relations of the Baltic states especially with the East and the West, study the transit position of the Baltics and briefly address their internal problems. For obvious reasons, we will focus on the decisive, not yet fully resolved multilateral relations with Russia.It is certain that the future of Estonia, Latvia and Lithuania will again be determined by basic geopolitical factors, primarily by the attitude of the West, but also by the political, economic and military development of their big neighbor - Russia. The internal politics of the Baltic states themselves, especially when it concerns the progress of the economy and democracy and relations with hundreds of thousands of mainly Russian immigrants (they were also called Soviet occupiers earlier), will certainly play a certain role in the overall development. However, it is known that the Baltic states are too insignificant and small - even if they cooperated intensively in a wide range of areas - for that; so that they build their future solely on their own efforts. The renewed independence of the Baltic states will therefore undoubtedly depend - just as it did in the interwar period - mainly on foreign goodwill and consent. In acquiring the necessary interface areas and tools for membership of the Baltic states in the Council of Europe will certainly help this purpose.It is certain that the long-term goal of the Baltic states lies first in association and later in membership in the European Union, the Western European Union and NATO. They want to anchor in Europe as soon as possible and if possible permanently.